PENTINGNYA VALUASI EKONOMI DALAM PENGELOLAAN KAWASAN KONSERVASI YANG LESTARI - Rachmansyah, Yanuar; Maryono, Joko (PRESTASI, 2010)
Economic valuation of natural resources and the environment needs to be done to provide total economic value. Understading the total economic value is expected to provide worthwhile information for wise management of natural resources and the environment. Economic valuation becomes an important tool in the management of natural resurces and the environment. However, economic valuation of natural resources and the environment is not an easy task. Conservation areas have been taken as an example of economic valuation. Some methods and techniques have been developed and used for valuing several resources. It is expected that Indonesian authority of natural resource and the environment to adopt the methods and use appropriately to provide better estimates of the total economic values.